2017
DOI: 10.1093/cid/cix018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Appropriateness of Urinary Catheters in Japanese Intensive Care Units: Results From a Multicenter Point Prevalence Study

Abstract: Urinary catheters were frequently used in the 7 participating Japanese intensive care units and almost half did not meet an appropriate indication for use. Overusing catheters for monitoring accurate input and output was especially notable. Multimodal interventions may be needed to limit inappropriate urinary catheter use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
3
15
0
1
Order By: Relevance
“…We previously found that urethral catheter use was higher and appropriate use was lower in Japanese ICUs compared to US ICUs. 4,5 After the intervention, the prevalence of urethral catheters (61%) and proportion used for appropriate indications (85%) was similar to rates found in US ICUs. Unlike the United States, healthcare worker awareness of nosocomial infection prevention practices in Asia is low.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We previously found that urethral catheter use was higher and appropriate use was lower in Japanese ICUs compared to US ICUs. 4,5 After the intervention, the prevalence of urethral catheters (61%) and proportion used for appropriate indications (85%) was similar to rates found in US ICUs. Unlike the United States, healthcare worker awareness of nosocomial infection prevention practices in Asia is low.…”
Section: Discussionsupporting
confidence: 58%
“…Unit nurses were required to attend a lecture about appropriate use of urethral catheters. Measuring hourly fluid balance in the critically ill is a commonly overused indication due to varied interpretations of being critically ill. 5 The Ann Arbor Criteria for Appropriate Urinary Catheter Use provides a clearer definition of urethral catheter use in critically ill patients, highlighting appropriateness when hourly measurement of urine volume is required to inform treatment. 7 Previously, we found that "immobility" was confused with immobilization required as part of treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 14–38% of the indwelling urethral catheters in hospitals are placed without a specific medical indication [7]. This percentage rises to almost 50% in the intensive care units [8]. The majority of all healthcare-associated urinary tract infections (UTIs) are caused by instrumentation of the urinary tract.…”
Section: Introductionmentioning
confidence: 99%